Contested Legitimacies Repression and Revolt in Post-Revolutionary Egypt - Grimm, Jannis Julien (Protest and Social Movements, 2022)
Since the military overthrow of President Mursi in mid-2013, Egypt has witnessed an authoritarian rollback. Through a combination of repression and nationalist securitizing discourses, popular pressure for reform was successfully channelled into a state-centric model of governance. But despite state violence and the restriction of public spaces, protests have anything but ceased. Contested Legitimacies explores this resilience of protest despite unprecedented repression through an approach attuned to the physical and discursive interactions among key players in Egypt's post-revolutionary arena. Starting with the successful Tamarod uprising against President Mursi, to the unsuccessful Islamist resistance against the military coup, to the Rabaa massacre and the shrinking spaces for protest under Al-Sisi's authoritarian rule, to the resurgence of popular resistance in the shape the Tiran and Sanafir island campaign, it investigates the rise and fall of different coalitions of contenders and explores their impact on Egypt's political transition.